Penerapan water tepid sponge terhadap suhu pada pasien dengue hemorrhagic fever dengan masalah hipertermia - Fitria, Yanti; Chrisanto, Eka Yudha; Kurniasih, Dennti (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Hyperthermia is a primary symptom found in all DHF patients. The duration of hyperthermia before treatment ranges from 2-7 days. Hyperthermia can be managed through non-pharmacological approaches, one of which is Water Tepid Sponge. Therefore, hyperthermia can be treated appropriately using comprehensive nursing care to lower the temperature to normal. Purpose: To provide nursing care to a client with dengue hemorrhagic fever who has hyperthermia, using the water tepid sponge technique. Method: This study used a descriptive research design with a case study design. The subjects were two individuals experiencing hyperthermia. This study was conducted in January 2025. The water temperature used in the compresses was between 350-370C, or lukewarm, and can be performed in approximately 15-20 minutes per session. Results: The author implemented water tepid sponge nursing care for three days in a patient with dengue hemorrhagic fever. The hyperthermia problems of both clients were resolved, as evidenced by Mrs. H and Mrs. S's body temperature was normal and the client was cooperative during both procedures. Conclusion: The application of water tepid sponges was effective in reducing hyperthermia in patients with dengue hemorrhagic fever. Keywords: Dengue Hemorrhagic Fever (DHF); Hyperthermia; Water Tepid Sponge. Pendahuluan: Hipertermia sebagai gejala utama terdapat pada semua penderita DHF. Lama hipertermia sebelum dirawat berkisar antara 2-7 hari. Mengatasi hipertermia melalui non farmakologi yang salah satunya adalah Water Tepid Sponge. Sehingga masalah hipertermi mendapat intervensi yang tepat dengan menggunakan asuhan keperawatan yang lengkap untuk menurunkan suhu menjadi normal. Tujuan: Untuk melakukan asuhan keperawatan pada klien dengue hemorrhagic fever dengan masalah keperawatan hipertermia dengan penerapan teknik water tepid sponge. Metode: Penelitian menggunakan desain penelitian deskriptif dengan rancangan studi kasus. Subjek yang digunakan 2 orang yang mengalami masalah keperawatan hipertermia. Penelitian ini dilakukan pada bulan Januari 2025. Suhu untuk air yang digunakan dalam kompres antara 350 -370C atau hangat hangat kuku, untuk pelaksanaannya dapat dilakukan dalam waktu sekitar 15-20 menit dalam 1 kali pelaksanaan. Hasil: Pengelolaan keperawatan hipertermia dengan penerapan tindakan keperawatan water tepid sponge yang penulis lakukan selama 3 hari pada pasien dengue hemorrhagic fever. Permasalah hipertermia kedua klien teratasi semua dibuktikan dengan klien Ny.H dan Ny. S suhu tubuhnya normal dan selama tindakan kedua klien kooperatif. Simpulan: Terdapat pengaruh penerapan water tepid sponge untuk mengurangi hipertermia pada pasien dengue hemorrhagic fever. Kata Kunci: Dengue Hemorrhagic Fever (DHF); Hipertermia; Water Tepid Sponge.